Investigations on electrical, electrochemical, and thermal properties of gelatine‑based novel biopolymer electrolytes for energy storage applications - C. Naveen; M. Muthuvinayagam; Khalid A. Alrashid; Saikh Mohammad; S. Vigneshwaran; SaravanaVadivu Arunachalam; Mohd Ikmar Nizam Mohamad Isa (Springer-Verlag GmbH Germany, 2024)
Indexed by WOS/ Scopus